Correlation of Clinical Presentation with Histopathological and Forensic Findings of Oral-Maxillofacial Injuries in Pediatric Abuse - Sibghatullah, Hadiya; Zafar, Amna; Afzal Memon, Haya; Rasool, Sohail; Sajid, Bushra; Masood, Barrira (Journal of Neonatal Surgery, 2025)
Introduction: Child abuse is a major public health issue, with oral and maxillofacial injuries frequently serving as early indicators of physical maltreatment. Accurate identification of these injuries is essential for timely intervention and legal documentation. Methods: A prospective observational study was conducted on 50 pediatric cases suspected of abuse in a tertiary care hospital of Pakistan from July 2025 to June 2025. Patients were evaluated for type, location, and severity of oral-maxillofacial injuries. Histopathological examination was performed on tissue samples where applicable, and forensic assessments were correlated with clinical findings to identify patterns indicative of inflicted trauma. Results: Specific injury patterns were identified, including lingual lacerations, palatal hematomas, and subperiosteal fractures. These injuries showed strong correlation with histopathological markers of blunt force trauma and forensic indicators consistent with non-accidental injury. Multidisciplinary evaluation improved the accuracy of detecting abuse and supported objective legal documentation. Conclusion: Integrating clinical, histopathological, and forensic assessments enhances early recognition of child abuse in cases presenting with oral-maxillofacial trauma. This approach facilitates timely protective interventions and strengthens medicolegal reporting, underscoring the importance of a coordinated multidisciplinary evaluation in suspected pediatric abuse